PENDAMPINGAN PEMBUATAN DESAIN DAN RAB UNTUK PEMBANGUNAN PONDOK PESANTREN KI AGENG SELO DUSUN SELOPURO DESA BALEREJO KEC. KEBONSARI KAB. MADIUN - Arif Afrianto; Rosyid Kholilur Rohman; Setiyo Daru Cahyono (JURNAL DAYA-MAS, 2023)
The difficulties experienced by managers in building planning are how to create architectural and functional building designs, how to plan and calculate the strength of the structure and how to calculate the construction costs. The design limitations of the Ki Ageng Selo Islamic Boarding School Gendung and the required Budget Plan (RAB), encouraged the enthusiasm of the Civil Engineering Study Program service team at Merdeka Madiun University to carry out the Assistance Service for the Construction of the RAB for the Ki Ageng Selo Islamic Boarding School Building. With the existence of the Ki Ageng Selo Islamic Boarding School Building as a place for educational services to the community, the development of the Ki Ageng Selo Islamic Boarding School in a more advanced direction towards an independent Islamic Boarding School will be even faster. The purpose of this service is to provide direction and assistance regarding development plans and budget plans so that the construction of the Ki Ageng Selo Islamic Boarding School can be realized as desired. The stages of implementing this activity are field surveys, collecting measurement data, analyzing the site and space circulation, making planning drawings. The design concept uses architectural aspects by considering lighting, air circulation and surrounding environmental conditions. Based on the results of the calculation of the budget plan (RAB), the Ki Ageng Selo Islamic Boarding School requires a total cost of IDR 1,516,114,093.00.